Didymin Suppresses Microglia Pyroptosis and Neuroinflammation Through the Asc/Caspase-1/GSDMD Pathway Following Experimental Intracerebral Hemorrhage - Gu, Lingui; Sun, Mingjiang; Li, Ruihao; Zhang, Xingyu; Tao, Yihao; Yuan, Ye; Luo, Xu; Xie, Zongyi (Frontiers in Immunology, 2022)
Neuroinflammation has been proven to exert an important effect on brain injury after intracerebral hemorrhage (ICH). Previous studies reported that Didymin possessed anti-inflammatory properties after acute hepatic injury, hyperglycemia-induced endothelial dysfunction and death. However, the role of Didymin in microglia pyroptosis and neuroinflammation after ICH is unclear. The current study aimed to investigate the effect of Didymin on neuroinflammation mediated by microglia pyroptosis in mouse models of ICH and shed some light on the underlying mechanisms. In this study, we observed that Didymin treatment remarkably improved neurobehavioral performance, decreased BBB disruption and brain water content. Microglia activation and neutrophil infiltration in the peri-hematoma tissue after ICH was strikingly mitigated by Didymin as well. At the molecular level, administration of Didymin significantly unregulated the expression of Rkip and downregulated the expression of pyroptotic molecules and inflammatory cytokines such as Nlrp3 inflammasome, GSDMD, caspase‐1, and mature IL-1β, TNF-α, MPO after ICH. Besides, Didymin treatment decreased the number of Caspase-1-positive microglia and GSDMD-positive microglia after ICH. Inversely, Locostatin, a Rkip -specific inhibitor, significantly abolished the anti-pyroptosis and anti-neuroinflammation effects of Didymin. Moreover, Rkip binding with Asc could interrupt the activation and assembly of the inflammasome. Mechanistically, inhibition of the Caspase-1 by VX-765 attenuated brain injury and suppressed microglia pyroptosis and neuroinflammation by downregulation of GSDMD, mature IL-1β TNF-α and MPO based on Locostatin-treated ICH. Taken together, Didymin alleviated microglia pyroptosis and neuroinflammation, at least in part through Asc/Caspase-1/GSDMD pathway via upregulating Rkip expression after ICH. Therefore, Didymin may be a potential agent to attenuate neuroinflammation via its anti-pyroptosis effect after ICH.